Answer:
x = 6 ; y = -9
Explanation:
8 x + 2 y = 30 ..........equ No 1
7 x + 2 y = 24......... equ No 2
8 x = 30 - 2y
∴ x =
![( 30 - 2 y)/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n21rcws35eqd8tbgmkq0ylkqb2dl3q4ava.png)
substituting the value of x in equ No 2
7
+ 2 y = 24
7 ( 30 -2 y) + 2 y × 8 = 24 × 8
7 × 30 - 14 y + 16 y = 192
210 + 2 y = 192
2 y = 192 - 210
2 y = - 18
∴ y = - 9
put y = -9 , 8 x = 30 - 2 y
8 x = 30 - 2 ( -9)
8 x = 30 - ( -18)
8 x = 48
∴ x = 6
x = 6 ; y = -9